Advances in selenium-containing brown rice protein: structural characteristics, functional modification, and applications - Shu Li; Xinjie Shang; Yaxin Wu; Yumeng Wang; Shiyu Lin; Zexu Li; Zhaohui Xu; Yixuan Li; Yao Tang; Rui Yang (Food Hydrocolloids, 2026)

Phosphorus availability overrides evolutionary adaptation to warming and high carbon dioxide in shaping diatom physiology and lipid metabolism - Mengcheng Ye; Peixuan Liu; Jiamin Lin; Siyu Luan; Meimei He; Tian Shen; Zexu Li; Bin Huang; Enqi Zhang; Junyan Li; Shuming Lin; Zihong Li; et al. (Limnology and Oceanography, 2026)
Rising ocean temperatures and CO 2 concentrations are reshaping phytoplankton physiology, yet how long‐term adaptation to these stressors interacts with nutrient limitation remains poorly understood. Phosphorus (P) frequently limits phytoplankton growth in coastal and stratified oceans, but it remains unclear whether adaptation to warming and elevated CO 2 modifies responses to P limitation and whether such adaptive advantages can be realized under nutrient stress. Here, we combined multi‐year experimental evolution of the model diatom Phaeodactylum tricornutum under warming, elevated CO 2 , and their combination with short‐term assays across a phosphorus gradient to examine how evolutionary history influences responses to P availability. Across all adaptation regimes, P availability overwhelmingly governed growth, photosynthetic performance, and lipidome structure. Long‐term adaptation increased maximum growth rate and phosphate affinity, but these advantages were largely suppressed under P limitation. Lipidomic analyses revealed extensive P‐driven membrane remodeling, characterized by declines in phospholipids and increases in glycolipids and neutral lipids. While lipid‐class remodeling remained highly conserved across adaptation regimes, structural lipid traits responded differently depending on both evolutionary history and phosphorus status. Under P‐replete conditions, warming and elevated CO 2 primarily promoted fatty‐acid elongation, whereas under P limitation they increased fatty‐acid desaturation. These results demonstrate that nutrient regimes constrain evolutionary responses to warming and elevated CO 2 , highlighting phosphorus as a key determinant of diatom resilience in future oceans. Increasing nutrient limitation in future oceans may therefore restrict the extent to which phytoplankton populations can realize adaptive advantages under climate change, with implications for marine productivity and biogeochemical cycling.

Fuzzy prescribed performance backstepping control for ship roll chaotic motion under actuator faults - Zexu Miao; Xianku Zhang; Daocheng Ma; Lin Qiao (Ocean Engineering, 2026)

Rapid evolution of marine phytoplankton under global change: mechanisms, constraints, and ecological consequences - Siyu Luan; Peixuan Liu; Bin Huang; Enqi Zhang; Junyan Li; Shuming Lin; Zihong Li; Tian Shen; Meimei He; Zexu Li; Jianrong Xia; Peng Jin (Marine Environmental Research, 2026)

Enhanced SO2 resistance of the Pd/Silicate-1 catalyst by rare earth oxide modification in methane combustion - Jinxiong Tao; Hongxia Lin; Yuxi Liu; Jiguang Deng; Lin Jing; Zhiwei Wang; Lu Wei; Zhen Wei; Zhiquan Hou; Zexu Zhang; Hongxing Dai (Journal of Environmental Sciences, 2026)

Phased Zero-Aquatic System Exchange in Shrimp Farming: A Farming Method Combining Sodium Humate and Bacillus - Shan Gao; Wuquan Liao; Yuhang Cui; Zexu Lin; Gang Shi; Ping Wang; Chengbo Sun (Journal of Ocean University of China, 2026)

HDAC9 Deficiency Upregulates cGMP-dependent Kinase II to Mitigate Neuronal Apoptosis in Ischemic Stroke - Haoran Lin; Yun Bei; Zexu Shen; Taofeng Wei; Yuyang Ge; Lingyan Yu; Huimin Xu; Wei He; Yunjian Dai; Difei Yao; Haibin Dai (Translational Stroke Research, 2025)

An Intriguing Structural Modification in Neutrophil Migration Across Blood Vessels to Inflammatory Sites: Progress in the Core Mechanisms - Zexu Wang; Yufang Guo; Yulei Zhang; Liangquan Wu; Li Wang; Qiuqi Lin; Bing Wan (Cell Biochemistry and Biophysics, 2024)

Germicidal effect of hydrogen peroxide nano-silver ion composite disinfectant and its effect on the microbial community of shrimp intestine and rearing water - Danqing Hou; Zexu Lin; Jianing Zhou; Yuan Xue; Chengbo Sun (Frontiers in Marine Science, 2023)
In this study, the inhibitory effect of different doses of hydrogen peroxide nano-silver ion composite disinfectant (HPS) on DIV1 and bacteria was analyzed, and the antibacterial activity of three disinfectants, HPS, potassium monopersulfate (KMPS) and calcium hypochlorite (Ca(ClO) 2 ), was compared. In addition, 16S rDNA amplification sequencing technology was used to analyze the effects of these three disinfectants on the intestinal microflora of Litopenaeus vannamei and the structure and composition of water microflora. The results showed that HPS did not positively affect the survival rate of prawns infected with DIV1, which needs to be verified in future studies. In the experimental design range, the higher the dosage of HPS, the more obvious the killing effect on the number of Vibrio and total bacteria in rearing water, and the two showed a negative correlation. 5,104 OTUs were obtained based on 16S rDNA high-throughput sequencing, of which 3,012 (59.01%) and 1,475 (28.90%) OUTs were annotated at the phylum and genus levels, respectively. Proteobacteria, Firmicutes, Actinobacteriota, Bacteroidetes, and Cyanobacteria dominated the water samples at the phylum level. At the genus level, the dominant bacterial genera in the intestinal bacterial community of shrimp were Photobacterium , Vibrio , and Ruegeria . The most dominant bacteria genera in water samples were Vibrio , Ruegeria , Pseudoalteromonas , and Nautella . In the water samples, the composition and structure of the Ca(ClO) 2 microbial community were relatively simple, and the species richness and diversity of Ca(ClO) 2 were significantly lower than those of HPS and KMPS disinfectant groups at 12 h and 24 h ( p < 0.05). In terms of inhibiting the diversity and richness of the microbial community, Ca(ClO) 2 had a significant effect ( p < 0.05), but the intestinal microbial community diversity of shrimp treated with HPS was higher than that of the other two groups. It is worth noting that, compared with the three disinfectants, HPS has the strongest killing effect on Vibrio and total bacteria, and has a certain positive significance for maintaining the stable state of the microbial community. This study provides a scientific basis for applying HPS in aquaculture and broadens the application range of HPS.

Dietary supplementation with chondroitin sulfate improved the growth, immunity, and intestinal microbiota structure of Penaeus monodon - Zexu Lin; Zihao He; Wuquan Liao; Minze Liao; Jianing Zhou; Yuan Xue; Chengbo Sun (Aquaculture, 2023)

Effects of sodium humate and probiotics on growth performance enzyme activity and microbial environment of Litopenaeus vannamei in high-density zero‐water exchange systems - Wuquan Liao; Zexu Lin; Minze Liao; Yuan Xue; Jianing Zhou; Yue Wang; Danqing Hou; Chengbo Sun (Frontiers in Marine Science, 2022)
The study investigates the outcomes of adding sodium humate and sodium humate with probiotics ( Lysinibacillus , Bacillus subtilis ) to culture water on the growth performance, enzyme activity, and microbial environment of shrimp. The sodium humate and probiotics concentrations were 3 mg/L and 10 5 CFU/mL in the culture water. Litopenaeus vannamei (0.31 ± 0.03 g) at a density of 300 shrimps/m 3 were cultured in nine buckets for a 43-days culture experiment. The results showed that the survival rate (SR) of L. vannamei in sodium humate group and sodium humate with probiotics group were (88.44%) and (86.07%), with the sodium humate group outcome being significantly better than the control group. The shrimps’ final body weight and specific growth rate (SGR) in the two experimental groups were significantly higher than the control group. The feed conversion rate (FCR) was significantly lower than the control group. The ammonia nitrogen concentration in sodium humate with probiotics group was significantly lower than the control group on the 15th day. The activities of intestinal amylase, lipase, trypsin and hepatopancreas superoxide dismutase (SOD), phenol oxidase (PO), and catalase (CAT) in sodium humate group were significantly higher than the control group. Notably, SOD, PO, and lipase activities in sodium humate with probiotics group were significantly higher than the control group. Illumina MiSeq high-throughput sequencing showed that the Chao and Ace indices of the culture water microflora in experimental groups were higher than the control group, and the sodium humate group was significantly higher than the control group. At the phylum level, Proteobacteria, Bacteroidetes, and Actinobacteria were the dominant bacterial communities in the intestine and culture water of L. vannamei , Proteobacteria was the most abundant phyla. At the genus level, the relative abundance of Pseudohongiella of water microflora in the control group was significantly lower than the experimental groups. Ruggiella (15.22-19.56%) was the most abundant genera of intestinal microflora. These results infer that the addition of sodium humate enhances the growth performance, digestive enzymes, and some immune enzyme activities, improving the richness of the water microbial community of L. vannamei .

Knockout of GGPPS1 restrains rab37-mediated autophagy in response to ventilator-induced lung injury - Zexu Wang; Meizi Chen; Xia Pan; Li Wang; Cheng Yin; Qiuqi Lin; Jingjing Jiang; Yunlei Zhang; Bing Wan (Human Cell, 2022)

Isobaric Tags for Relative and Absolute Quantitation-Based Proteomics Analysis Provides a New Perspective Into Unsynchronized Growth in Kuruma Shrimp (Marsupenaeus japonicus) - Jichen Zhao; Minze Liao; Zexu Lin; Yiyi Huang; Yunqi Zhong; Luyao Liu; Guoliang Chen; Zuotao Ni; Chengbo Sun (Frontiers in Marine Science, 2021)
Unsynchronized growth is a common phenomenon in farmed crustaceans. The underlying molecular mechanism of unsynchronized growth of crustaceans is unclear. In this study, a comparative proteomic analysis focusing on growth differences was performed using kuruma shrimp Marsupenaeus japonicus , an economic crustacean species, as the model. The study analyzed kuruma shrimp at fast growth stage and steady growth stage from both fast growth group and slow growth group by an Isobaric tags for relative and absolute quantitation (iTRAQ)-based quantitative proteomic analysis method. A total of 1,720 proteins, including 12,291 peptides, were identified. Fifty-two and 70 differentially expressed proteins (DEPs) were identified in the fast growth stage and steady growth stage, respectively. Interestingly, 10 DEPs, including 14-3-3-epsilon-like, GPI, GPD1, MHC-1a, and MHC-1b, were presented in both growth stages. In addition, all these 10 DEPs shared the same expression tendency at these two growth stages. The results indicated that these 10 DEPs are potential growth biomarkers of M. japonicus . Proteins associated with faster growth of M. japonicus may promote cell growth and inhibit cell apoptosis through the Hippo signaling pathway. The fast growth group of M. japonicus may also achieve growth superiority by activating multiple related metabolic pathways, including glycolysis, glycerophospholipid metabolism and Citrate cycle. The present study provides a new perspective to explore the molecular mechanism of unsynchronized growth in crustacean species.